(untitled) (Pravaha, 2024)
This article analyses the effectiveness of Business Development Services (BDS) to promote micro-enterprises in Kavre District of Nepal implemented by the Ministry of Industry’s Micro Enterprise Development Program (MEDEP). Business Development Services generally composes various support services required by start-up entrepreneurs during the enterprise creation and growth stages. Opinion surveys of micro-entrepreneurs were conducted to assess the effectiveness of enterprise development services rendered to them on the growth and sustainability of their enterprises. All the six components of the BDS package have helped enhance the growth and sustainability of micro-enterprises in Kavre.